A Comparison of AIMSWeb TEL and PALS-K Reading Assessments - Gehring, Allison K.; Butterfuss, Reese M. (My University, 2014)
Response to Intervention (RtI) practices in educational settings aim to identify students who are at risk for academic struggle. Typically, RtI tries to identify 20% of students as at-risk (Good, Simmons, & Smith, 2008). It is crucial to provide at-risk students with early interventions to prevent student failure (Hughes & Dexter, 2014). Standardized screening assessments are used in identifying students who are at-risk for failure. To successfully identify at-risk students, screeners must be reliable, valid, accurate, and inexpensive. This study addresses two questions. One, how well does each screener correctly predict which children will perform below expectation (i.e. "at-risk" children) on grade 1 reading measures? And two, which kindergarten subtests are most predictive of first-grade reading performance?
Color poster with text and tables.
Keywords: Literacy; Reading assessments; Phonological Awareness Literacy Screening-Kindergarten (PALS-K); AIMSWeb; Posters